Regulatory Stewardship of Health Research: Navigating Participant Protection and Research Promotion - Edward S. Dove (Edward Elgar Publishing, 2020)
This timely book examines the interaction of health research and regulation with law through empirical analysis and the application of key anthropological concepts to reveal the inner workings of human health research. Through ground-breaking empirical inquiry, Regulatory Stewardship of Health Research explores how research ethics committees (RECs) work in practice to both protect research participants and promote ethical research. This thought-provoking book provides a new perspective on the regulation of health research by demonstrating how RECs and other regulatory actors seek to fulfil these two functions by performing a role of 'regulatory stewardship'.